Design of Performance Measurement Instrument at The Work Unit of Adisutjipto Institute of Aerospace Technology Yogyakarta - Yasrin Zabidi; Marni Astuti (Institute of Computer Science (IOCS), 2022)
The problem in this research is that there is no performance measurement in the work unit of the Adisutjipto Institute of Aerospace Technology (ITDA). This study aims to design a performance measurement instrument to measure performance in the ITDA work unit. The method used in designing the performance measurement instrument is the balanced scorecard and Objective Matrix (OMAX) method. The results obtained from this study, there are 7 Performance Indicators (IK), namely, the percentage increase in the budget, the percentage of budget absorption, the user/customer satisfaction index, the number of complaints,, the percentage of the implementation of the work program against the planned work program, percentage of conformity of work carried out with existing job description documents, and job satisfaction index. This research also produces worksheets/performance measurement instruments that can be used to measure the performance of work units in ITDA. Based on the worksheets/performance measurement instruments, it was obtained that IK 1 was good, IK 2 was very good, IK 3 was good, IK 4 was moderate, IK 5 was very good, IK 6 was very good, and IK 7 was good. Overall good performance score.